Chiretta Cream / Amyra Hazwani Ghazali, Caroline U. P. and Nur Syahirah U. - Ghazali, Amyra Hazwani; U. P., Caroline; U, Nur Syahirah (Faculty of Plantation and Agrotechnology, 2023)
Green Chiretta or hempedu bumi, which has long been used to treat inflammation and infection, has been demonstrated to have anti-bacterial efficacy against a variety of bacteria in extract form. The purpose of this research is to look into the anti-bacterial characteristics of Green Chiretta against escherichia coli (E. coli) and to manufacture Green Chiretta into cream to determine its anti-bacterial qualities.